DIGITAL ENTREPRENEURSHIP EDUCATION: THE DEVELOPMENT OF AN INSTAGRAM-BASED TRAINING MODULE FOR YOUTH - Jerry Rommy Herter Wuisang (EDUCATIONE, 2026)
Youth unemployment and underemployment remain persistent in developing contexts, calling for scalable, engaging entrepreneurship education that aligns with Gen-Z’s digital habits. This study aimed to develop and validate an Instagram-based training module to strengthen entrepreneurial attitudes and behaviors among young MSME actors in Tondano, Indonesia. Using a Research & Development approach with the 4-D model (Define–Design–Develop; Disseminate planned), we conducted needs analysis, iterative prototyping, expert validation (content and media), and pilot testing with purposively sampled participants (n = 30; ages 18–30). Data were gathered via Likert-type questionnaires and Focus Group Discussions and analyzed descriptively with percentage criteria for feasibility. Results show high feasibility and acceptance: material validation = 90.34% (very good), media validation = 82% (good), platform/Instagram usability = 92.5% (very good); user responses indicated 92.5% strongly agree and 7.5% agree that the module improved understanding of entrepreneurial attitudes/behaviors. We conclude that an Instagram-based, micro-modular design is practicable, context-fit, and engaging for youth entrepreneurship learning. Practically, the module offers a low-cost, mobile, and scalable alternative for educators, community organizations, and local governments to complement formal programs and expand outreach. Future research should (a) conduct larger multi-site trials, (b) embed formal assessment (e.g., quizzes, performance tasks) and gamified elements, (c) evaluate longitudinal outcomes (self-efficacy, venture activity), and (d) compare cross-platform delivery (e.g., TikTok/YouTube/LMS) to mitigate algorithmic visibility bias.